EVALUASI USER INTERFACE DAN USER EXPERIENCE PADA WEBSITE BRISMART MENGGUNAKAN USABILITY TESTING DENGAN METODE SYSTEM USABILITY SCALE (SUS) (STUDI KASUS PESERTA MAGANG KAMPUS MERDEKA PT. BANK RAKYAT INDONESIA) - Gabriella Clarissa Leandra (2023)
The presence of Learning Management System (LMS) at PT. Bank Rakyat Indonesia assists in monitoring how users access materials in E-Learning. The results of a survey of BRISmart users show that there are several problems experienced by users such as feeling that the card is too integrated with the background and not knowing there is a profile page. For this reason, as a learning support service at BRI, BRISmart requires a usability level measurement that aims to find problems that cannot be seen directly. The evaluation is carried out using Usability Testing with the system Usability Scale (SUS. The evaluation was carried out on independent campus interns with three stages, namely usability testing, in-depth interview and post testing questionnaire. This evaluation process refers to three aspects of usability, namely effectiveness, efficiency, and user satisfaction. The results of the current BRISmart website evaluation say that there are several problems experienced such as features that are not widely known by users and also users feel the appearance of the BRISmart website is less user friendly. After the BRISmart website redesign, a comparison was obtained between the current BRISmart website evaluation and the BRISmart website redesign which showed an improvement in the overall task, namely in the effectiveness aspect each task gets 100% results, the efficiency aspect increases from 5.02 to 17.53 seconds, and the user satisfaction aspect increased by 37.16 from 43.23 to 80.39 and entered grade A which is acceptable.